Communication in The Perspective of The Country - I Nyoman Indra Kumara; Nuning Indah Pratiwi; Anak Agung Sagung Mirah Pertiwi (Universitas Pendidikan Nasional, 2022)
The aim of this study was to determine the forms of political communication through the mass media. Political communication is very important in determining democratization. With competition in politics, there will also be communication competition that occurs to influence, acquire, maintain, and expand power. The phenomenon of political communication is very influential in the real world, including political communication in the mass media. This research is qualitative research with a descriptive approach using three data collection techniques, namely interviews, observation, and documentation. From the three data collection techniques, it was found that political communication through mass media was often carried out by party officials in order to increase credibility and legitimacy both personally and institutionally.